The relevance of the world council of churches in global ecumenism: an African overview (2011)
The effects of Reformation masterminded by Martin Luther in the sixteenth century cannot be underestimated. Apart from different opinions held by the Catholic Church and the Reformers, various denominations emerged within the latter because each one separated from the rest. Such separation and lack of mutual trust and understanding existed for centuries before the “Spirit of Ecumenism” fell on Church leaders. In the sixteenth century, only four major divisions separate the churches of the Reformation: Lutheran, Reformed, Anabaptist and Anglican. Soon, however, a number of denominations appeared on the scene, most of them established by adherents convinced of the importance of some particular teachings of scripture. By the twentieth century, more than two hundred denominations crowded the landscape in the United States alone. In the same century however, a force drew Christians toward co-operation, merger and united action. This force f is referred to as “ecumenism”. Therefore this paper highlights the contribution of the World Council of Churches to Ecumenism project. It concludes that the reason for the reestablishment of the WCC has not been justified, owing to the prevalence of the wounds created by schism and lack of its impact on grassroots churches.